Study of Best Antenna Configuration for Axillary Microwave Imaging Prototype - Godinho, Daniela M. (2024)
Imaging the axillary region for detection of axillary lymph nodes metastasised by breast cancer is currently under development using microwave signals. A limited angular view justifies the study of the best antenna configuration for this application. In this paper, we perform a preliminary study to find the best antenna configurations for axillary microwave imaging. The results show the quality of target detection is affected by the choice of antenna configurations, and also that it depends on the position of the target. One of the potential candidates for antenna configuration shows promising results.